Distance, Smoking Habits, and Carboxyhemoglobin Levels in Male Students: Jarak, Kebiasaan Merokok, dan Tingkat Karboksihemoglobin pada Mahasiswa Laki-laki - Verindah, Reza; Hanum, Galuh Ratmana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Carboxyhemoglobin (COHb) formation occurs when carbon monoxide (CO) binds with hemoglobin, showing an affinity 200–300 times stronger than oxygen, which disrupts oxygen transport and utilization in the body. Specific Background: In urban environments, CO exposure may be influenced by lifestyle factors such as daily travel distance and smoking habits, both of which are suspected contributors to elevated COHb levels. Knowledge Gap: Despite known toxicological effects of CO, limited research addresses how these lifestyle factors correlate with COHb levels in young adults, particularly male health students. Aim: This study investigated the association between distance traveled and smoking habits with COHb levels among male students of the Faculty of Health Sciences, Muhammadiyah University of Sidoarjo. Results: Findings showed that all respondents (100%) had COHb levels below the standard threshold (<3.5%) set by the Indonesian Ministry of Health Regulation No. 70 of 2016, and statistical analysis indicated no significant association between either variable and COHb levels (p>0.05). Novelty: This research highlights that common risk factors like smoking and travel distance may not always predict elevated COHb in health student populations. Implications: The results provide reassurance regarding current exposure levels and may guide preventive health education for student populations. Highlights: All respondents had COHb levels below the national threshold. No significant association was found between smoking or travel distance and COHb. Provides baseline data for health education and preventive strategies. Keywords: Carboxyhemoglobin; Carbon Monoxide; Smoking; Travel Distance; Toxicology